2004
DOI: 10.1051/0004-6361:20040380
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Mg IX photorecombination rate coefficient

Abstract: Abstract. The rate coefficient for radiative and dielectronic recombination of beryllium-like magnesium ions was measured with high resolution at the Heidelberg heavy-ion storage ring TSR. In the electron-ion collision energy range 0-207 eV resonances due to 2s → 2p (∆N = 0) and 2s → 3l (∆N = 1) core excitations were detected. At low energies below 0.15 eV the recombination rate coefficient is dominated by strong 1s 2 (2s 2p 3 P) 7l resonances with the strongest one occuring at an energy of only 21 meV. These … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
96
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(98 citation statements)
references
References 33 publications
(63 reference statements)
2
96
0
Order By: Relevance
“…Overall, we estimate the accuracy of our predicted DR rate coefficients to be ≈±20% for temperatures above a few eV. We note, however, that storage ring results for Fe ions with different charge have demonstrated that all state-of-the-art theoretical methods (e.g., MCBP, MCDF, HULLAC, R-matrix, and FAC) are not able to reproduce reliably the DR resonance strengths and energies of L-shell ions for relative collision energies < ∼ 1 eV due to the limitations of the accuracies of the low-lying resonances theoretical energies (e.g., Savin et al 1999;Schippers et al 2001;Savin et al 2002b;Schippers et al 2004) due to the limitation of the accuracies of the low-lying resonance theoretical energies. The theoretical DR rate coefficients below ≈1 eV should be used with extra caution, and for reliable total DR rate coefficients at plasma temperatures where these resonances play a significant role, these MCBP results need to be supplemented with storage ring measurements of the relevant resonances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, we estimate the accuracy of our predicted DR rate coefficients to be ≈±20% for temperatures above a few eV. We note, however, that storage ring results for Fe ions with different charge have demonstrated that all state-of-the-art theoretical methods (e.g., MCBP, MCDF, HULLAC, R-matrix, and FAC) are not able to reproduce reliably the DR resonance strengths and energies of L-shell ions for relative collision energies < ∼ 1 eV due to the limitations of the accuracies of the low-lying resonances theoretical energies (e.g., Savin et al 1999;Schippers et al 2001;Savin et al 2002b;Schippers et al 2004) due to the limitation of the accuracies of the low-lying resonance theoretical energies. The theoretical DR rate coefficients below ≈1 eV should be used with extra caution, and for reliable total DR rate coefficients at plasma temperatures where these resonances play a significant role, these MCBP results need to be supplemented with storage ring measurements of the relevant resonances.…”
Section: Discussionmentioning
confidence: 99%
“…The published high-temperature DR rate coefficients for fluorine-like ions vary by up to a factor of 4.7. Recent experimental measurements (Savin et al 1997(Savin et al , 1999(Savin et al , 2002a(Savin et al ,b, 2003Schippers et al 2001Schippers et al , 2004 have also shown that many of the earlier computations of low temperature DR rate Present Address: Physics Department, Drake University, Des Moines, IA 50311, USA e-mail: oleg_zoi@yahoo.com coefficients are inaccurate. Taken altogether, it is clear that systematic computations with improved approximations are needed.…”
Section: Introductionmentioning
confidence: 99%
“…In this energy range, the discrepancies between measured and calculated results are even larger, which lead to a profound impact on the low-temperature plasma rate coefficients. Even a small variation in low-energy DR resonance positions may induce an uncertainty of a factor 2-3 in the plasma rate coefficients (Schippers et al 2004). The recombination rate coefficients obtained from measurements at storage rings are accurate enough and can be used to benchmark different theoretical descriptions.…”
Section: Introductionmentioning
confidence: 99%
“…At these very low energies, the DR plasma rate coefficients are very sensitive to the energy position of the resonances. A few meV uncertainty in the position of DR resonances changes the low-temperature plasma DR rate coefficients by an order of magnitude (Schippers et al 2004). A critical evaluation of the uncertainties in the existing calculated high-temperature DR rate coefficients has been performed by Savin & Laming (2002).…”
Section: Introductionmentioning
confidence: 99%